Early-life stress affects drug abuse susceptibility in adolescent rat model independently of depression vulnerability - Alves, Renata L. (2020)
The development of substance abuse problems occurs due to a diverse combination of risk factors. Among these risks, studies have reported depression and early-life stress as of importance. These two factors often occur simultaneously, however, there is a lack of understanding of how their combined effect may impact vulnerability to drug abuse in adolescence. The present study used rats with different vulnerability to depression (Wistar and Wistar-Kyoto) to investigate the impact of maternal separation (MS) on emotional state and drug addiction vulnerability during the adolescence period. Mothers and their litters were subjected to MS (180 min/day) from postnatal day 2 to 14. The offspring emotional state was assessed by observing their exploratory behavior. Drug abuse vulnerability was assessed through conditioning to cocaine. MS impacted the emotional state in both strains. Wistar responded with increased exploration, while Wistar-Kyoto increased anxiety-like behaviours. Despite the different coping strategies displayed by the two strains when challenged with the behavioural tests, drug conditioning was equally impacted by MS in both strains. Early-life stress appears to affect drug abuse vulnerability in adolescence independently of a depression background, suggesting emotional state as the main driving risk factor.